(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The given article underlined the significance of identifying learning styles in order to be more productive in the period of studying foreign languages. People receive and process information in different ways. It is mainly associated with individuals the way of applying data by their sensory modalities such as seeing, hearing, and touching. Learning styles are the manners and approaches in which learners learn best. In this research, I will review the learning styles based on several theories following the importance they have in the application in learning and teaching a second language process